Exploring the Invisible Vulnerability and Stigma of Male Sex Workers - Khatun, Rinki (Journal of Educational Research and Policies, 2024)
Since the beginning of time, prostitution has existed in our civilization. The oldest and the most traditional job is prostitution, according to history. Earlier writings and mythology also refer to it. Celestial demigods, which include Menaka, Rambha, Urvashi, & Thilothamma, who engage in high - class prostitution, are depicted in Indian mythology as being prostitutes. With impressive musical and dance abilities, they are the epitome of feminine appeal. Having multiple sex relationships, especially for financial gain, is prostitution. Major prostitution hotspots may be found all over India, making it a fairly common activity. In addition to traditional prostitution rings, one can also locate prostitutes in places like brothels, massage parlors, online travel agencies, clubs, and pubs. Now, unlike in the past, anyone can become a prostitute. Additionally, men and transgender people have entered the market for selling their physiques for cash. The number of men who engage in prostitution is growing; some do so out of necessity for money, while others are 'forced' into it. As implied by the phrase "forced, " men are coerced into prostitution against their will and forced to engage in sexual activity with women, men, as well as transgender people. The reality of male sex labor, both forced and consensual, is frequently overlooked in discussions about gender rights and challenges. These young males are often forced into prostitution without resorting to physical force; instead, non - violent methods are employed. The majority of men engage in prostitution freely, mainly to make money. Some are prepared to work as homosexual prostitutes when offered a job online. These individuals are attracted to the West by the prospect of a better future, and as a result, they frequently take out loans with excessive interest rates. It is practically hard for them to repay the debt because they must labor for an inadequate salary when they arrive. The brothel operators have forced men to comply by seizing passports and threatening to reveal the men's families. Sex workers are not merely passive beneficiaries of the trade; they frequently have many identities, including that of siblings, parents, sisters, and brothers, and they often live in families. Additionally, it has been observed that sex workers frequently work outside brothels. Men forced into the sex industry frequently suffer since there is no standardized effort to safeguard or rehabilitate them. Most are engaged in the male sexual trade at night while working in different daily roles. Their daily lives continue while the circumstance keeps happening over and over again. Men who sold sex in nations where sexual minorities have been prosecuted or decriminalized instead of legalized found this to be particularly relevant. These results demonstrate the necessity for suitable sex worker support designed to handle the particular problems faced by male sex workers. Since it is still a taboo subject, it is an intriguing research topic and is thus explored in my study. In order to identify potential gaps in literature, help define new research possibilities, and direct the development of public health policy, this article aims to identify and integrate these emergent discoveries. It will explores several recent developments in the male labor market. Notably, globalization and technology have changed the environment in which the male sex business functions and helped to normalize male - sex employment.